EFFECTIVENESS OF TALKING CURE THERAPY IN DEALING WITH TRAUMA AMONGST JOURNALISTS IN KENYA - Mutua, Joan; Mberia, Dr .Hellen K.; Minja, Prof. David (International Journal of Psychology, 2016)
Methodology: This study adopted mixed methods (qualitative and quantitative) with bias towards quantitative. Data was collected using both interviews and questioners. Data collected was cleaned, coded and analyzed using statistical package for social sciences (SPSS). The data was presented using both qualitative and quantitative statistics. Results: The study found that talking cure therapy is a good strategy of dealing with trauma among journalists. Unique contribution to theory, practice and policy: The study recommends that journalist should talk about their traumatic experiences. This will help them in dealing with trauma. In addition media houses should look for talking platforms for journalists to talk about their traumatic experiences.